Membangun Kesadaran Remaja tentang Bahaya Seks Bebas Terhadap Kehamilan yang Tidak Diinginkan - Insaniyah, Khafidhiyah Nur; Supriyanti, Eka; Fahmi, Nahdia Aulia (Universitas Pahlawan Tuanku Tambusai, 2026)
Adolescence is the transition from childhood to adulthood, occurring between the ages of 10 and 19. Adolescents are vulnerable to promiscuous sexual behavior, which can result in unwanted pregnancies. Globally, the number of unwanted pregnancies reaches 200 million (38%) per year among those aged 15 and 19. Causes of promiscuous sexual behavior include: knowledge, self-control, family, social media, and peers. The high rate of unwanted pregnancies must be addressed immediately. The purpose of this activity is to raise adolescent awareness of the dangers of promiscuous sex, which can lead to unwanted pregnancies, through Comprehensive Sexuality Education (CSE). Community service was carried out at the MADANI Indonesia Health Vocational School with 69 students. The method used was reproductive health education through lectures, discussions, questions and answers, and evaluation using a pre-test and post-test to measure changes in knowledge and attitudes. The results showed an increase in good knowledge from 26.09% to 82.61% and an increase in positive attitudes from 60.87% to 100%. These findings indicate that the CSE approach is effective in increasing adolescent knowledge and positive attitudes regarding the dangers of promiscuous sex.